PARTISIPASI MASYARAKAT DALAM PROGRAM BANTUAN LANGSUNG PAKAN SAPI PERAH DI DUSUN WATES DESA SUMOGAWE KECAMATAN GETASAN - Ayuk Mutiara Saraswati; Tinjung Mary Prihtanti (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2015)
The purpose of the study to know the process and the level of participation from the planning to the implementation of the program of direct assistance to strengthen the animal feed dairy cows; and to determine the factors driving and inhibiting factors of community participation in strengthening Assistance Program Dairy Cattle Feeding, by taking the research location in the Wates, Sumogawe Village, District Getasan, Semarang regency. The study revealed that: (1) Public participation at the program includes involvement in the stage of socialization activities; implementation; monitoring; and evaluation activities; (2) Participation of farmers in the form of aspiration in determining the location, involvement given in the implementation of activities,participation forage material, and social participation that is mutually assist in the implementation of the program and solve problems together; (3) The level of public participation in the program when compared with eight rungs Arnstein only until consulting level; (4) The driving factors for community participation in the Strengthening Aid Dairy Cattle Feeding Program a) The assistance provided free of charge, and the necessary requirements are not difficult; b) The program in accordance with the needs of the community members; c) extension workers willing to provide regular guidance to farming group; d) the location was available forage; e) Intertwined good cooperation and communication relations between farmer with field officers. Factors inhibiting a) in evaluating the feeling lazy in preparing reports on the production of milk; b) farmer with higher avoid to join because already have a high income; and c) limited quantity of assistance was raised the existence of envy.